Penegakan Hukum Terhadap Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan Kampus Undana Kupang - Sogen, Elisabeth Sanctris; Masu, Renny Rebeka; Resopijani, A (Law Faculty, Nusa Cendana University, 2024)
This research was conducted in the Nusa Cendana University Kupang campus. The background to this research is that campuses are a place to study but there are also perpetrators of sexual violence. The problems studied are: (1) How is law enforcement regarding the prevention and handling of sexual violence in the Undana Kupang Campus environment, (2) What are the procedures for handling sexual violence in the Undana Kupang campus environment. This research is a descriptive analysis research using a normative juridical approach method that analyzes and examines Nusa Cendana University Chancellor's Regulation No. 8 of 2022. The research results show that: (1) Law enforcement regarding the prevention and handling of sexual violence in the Undana Kupang Campus environment has been implemented through Undana Chancellor's Regulation No. 8 of 2022 and has been implemented in Undana, from this Chancellor's Regulation a special Task Force has been formed to handle the problem of sexual violence in Undana. (2) Procedures for handling sexual violence within the Undana Kupang Campus have been carried out properly by the Task Force. This shows that it is important for Undana Higher Education to require Chancellor's Regulation No. 8 of 2022 is included in general courses and create a guidebook on preventing and handling sexual violence for all parties within the Undana campus.